2016
DOI: 10.18203/2320-6012.ijrms20161914
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian hormone in health and disease: a review

Abstract: Anti-Müllerian hormone (AMH) is a homodimeric glycoprotein, member of the transforming growth factor β family of growth and differentiation factors. In the ovary, AMH has an inhibitory effect on primordial follicle recruitment as well as on the responsiveness of growing follicles to follicle-stimulating hormone (FSH). The ovary-specific expression pattern in granulosa cells of growing non-selected follicles makes AMH an ideal marker for the size of the ovarian follicle pool. AMH levels accurately reflect the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…AMH levels seem to be an early, reliable and (in)direct indicator of declining ovarian function, very useful in the clinical setting when evaluating fertility in women. 4 , 6 Hamdine et al (2015) demonstrated that AMH is an adequate predictor for both high and low response in gonadotropin-releasing hormone (GnRH) antagonist cycles for assisted reproductive techniques (ART) and the optimization and individualization of this protocols may be improved by using an AMH-tailored approach. 7 A systematic review and meta-analysis performed in 2022 revealed that AMH had better prediction for live birth in advanced age women and may have implicative predictive value for assisted conception counseling of couples of advanced ages when performing ART.…”
Section: Introductionmentioning
confidence: 99%
“…AMH levels seem to be an early, reliable and (in)direct indicator of declining ovarian function, very useful in the clinical setting when evaluating fertility in women. 4 , 6 Hamdine et al (2015) demonstrated that AMH is an adequate predictor for both high and low response in gonadotropin-releasing hormone (GnRH) antagonist cycles for assisted reproductive techniques (ART) and the optimization and individualization of this protocols may be improved by using an AMH-tailored approach. 7 A systematic review and meta-analysis performed in 2022 revealed that AMH had better prediction for live birth in advanced age women and may have implicative predictive value for assisted conception counseling of couples of advanced ages when performing ART.…”
Section: Introductionmentioning
confidence: 99%
“…3 It is a homodimeric glycoprotein belonging to the transforming growth factor-β (TGF-β) super family. 4 AMH has been reported to fall to very low levels as early as 5 years prior to the final menstrual period and ovarian production of AMH ceases as women enter menopause. This is a continuum rather than an abrupt event.…”
Section: Introductionmentioning
confidence: 99%